Cognitive and psychosocial development of HIV pediatric patients receiving highly active anti-retroviral therapy: a case-control study - Theodoridou Maria; Kafetzis Dimitrios A; Spoulou Vassiliki; Critselis Elena; Bertou Georgia; Thomaidis Loretta (BMC, 2010)
Abstract Background The psychosocial development of pediatric HIV patients has not been extensively evaluated. The study objectives were to evaluate whether emotional and social functions are differentially associated with HIV-related complications. Methods A matched case-control study design was conducted. The case group (n = 20) consisted of vertically infected children with HIV (aged 3-18 years) receiving HAART in Greece. Each case was matched with two randomly selected healthy controls from a school-based population. CNS imaging and clinical findings were used to identify patients with HIV-related neuroimaging abnormalities. The Wechsler Intelligence Scale III and Griffiths Mental Abilities Scales were applied to assess cognitive abilities. The age specific Strengths and Difficulties Questionnaire was used to evaluate emotional adjustment and social skills. The Fisher's exact test, student's t-test, and Wilcoxon rank sum test were used to compare categorical, continuous, and ordinal scores, respectively, of the above scales between groups. Results HIV patients without neuroimaging abnormalities did not differ from patients with neuroimaging abnormalities with respect to either age at HAART initiation (p = 0.306) or months of HAART treatment (p = 0.964). While HIV patients without neuroimaging abnormalities had similar cognitive development with their healthy peers, patients with neuroimaging abnormalities had lower mean General (p = 0.027) and Practical (p = 0.042) Intelligence Quotient scores. HIV patients without neuroimaging abnormalities had an increased likelihood of both Abnormal Emotional Symptoms (p = 0.047) and Hyperactivity scores (p = 0.0009). In contrast, HIV patients with neuroimaging abnormalities had an increased likelihood of presenting with Abnormal Peer Problems (p = 0.033). Conclusions HIV patients without neuroimaging abnormalities are more likely to experience maladjustment with respect to their emotional and activity spheres, while HIV patients with neuroimaging abnormalities are more likely to present with compromised social skills. Due to the limited sample size and age distribution of the study population, further studies should investigate the psychosocial development of pediatric HIV patients following the disclosure of their condition.